STUDI PERBANDINGAN TENTANG KAFA-AH DALAM HUKUM ISLAM DAN BUDAYA BUGIS BONE - said, ali (Pasca Sarjana STAIN Watampone, 2016)
Research results show kafÄâah that is recommended by Islam in selecting prospective spouses, but it can be a valid size or whether the marriage. kafÄâah was the right woman or his guardian.